Malaysia healthcare system = Malezya saglik sistemi - Che Musa, Muhd Firdaus (BIOSAD.org., 2017)
Malaysia is an upper middle-income country that enjoys political and economic stability. Malaysian population is young, growing or ageing. In recent years, the life expectancy at birth is 73 years. Malaysia has fostered various collaborations and partnerships with international associations, such as the WHO, Association of Southeast Asian Nations (ASEAN) and others in its effort to improve general health. Consequently, the country has benefi ted from a well-developed health care system, good access to clean water and sanitation, non-communicable diseases now account for most mortality and morbidity while communicable diseases still remain a concern. Malaysia’s public health system is organized under a civil service structure and are centrally administered by the Ministry of Health [MOH] and fi nanced mainly through general revenue and taxation, while the private sector is funded through private health insurance and out-of pocket payments from consumers. Furthermore, only a limited number of private organisations (employers)provide dental insurance that provides subsidises dental care that suggests that there is some limitation for dental care due to fi nancial costs. Meanwhile, the supply of health professionals has increased over the years, as the result of the government’s effort to increase medical/dental training facilities, although its number is still below the required number. As the country approaches developed nation status, its demographic and epidemiological transitions will continue and the demand for health care by the population continues to rise and further heighten expectations for more high quality of health care. These place pressure for Malaysia for health reform in the year 2020 and beyond.